The environmental pollutant and tobacco smoke constituent dibenzo[def, p]chrysene is a co-factor for malignant progression of mouse oral papillomavirus infections. (5th January 2021) - Christensen, Neil D.; Chen, Kun-Ming; Hu, Jiafen; Stairs, Douglas B.; Sun, Yuan-Wan; Aliaga, Cesar; Balogh, Karla K.; Atkins, Hannah; Shearer, Debra; Li, Jingwei; Brendle, Sarah A.; Gowda, Krishne; et al.
Abstract: HPV infections in the oral cavity that progress to cancer are on the increase in the USA. Model systems to study co-factors for progression of these infections are lacking as HPVs are species-restricted and cannot grow in preclinical animal models. We have recently developed a mouse papillomavirus (MmuPV1) oral mucosal infection model that provides opportunities to test, for the first time, the hypothesis that tobacco carcinogens are co-factors that can impact the progression of oral papillomas to squamous cell carcinoma (SCC). Four cohorts of mice per sex were included: (1) infected with MmuPV1 and treated orally with DMSO-saline; (2) infected with MmuPV1 and treated orally with the tobacco carcinogen, dibenzo[ def, p ]chrysene (DBP); (3) uninfected and treated orally with DMSO-saline, and (4) uninfected and treated orally with DBP. Oral swabs were collected monthly for subsequent assessment of viral load. Oral tissues were collected for in situ viral DNA/RNA detection, viral protein staining, and pathological assessment for hyperplasia, papillomas and SCC at study termination. We observed increased rates of SCC in oral tissue infected with MmuPV1 and treated with DBP when compared to mice treated with DBP or virus individually, each of which showed minimal disease. Virally-infected epithelium showed strong levels of viral DNA/RNA and viral protein E4/L1 staining. In contrast, areas of SCC showed reduced viral DNA staining indicative of lower viral copy per nucleus but strong RNA signals. Several host markers (p120 ctn, p53, S100A9) were also examined in the mouse oral tissues; of particular significance, p120 ctn discriminated normal un-infected epithelium from SCC or papilloma epithelium. In summary, we have confirmed that our infection model is an excellent platform to assess the impact of co-factors including tobacco carcinogens for oral PV cancerous progression. Our findings can assist in the design of novel prevention/treatment strategies for HPV positive vs. HPV negative disease. Graphical abstract: Image 1 Highlights: Increased rates of oral cancer in mice infected with MmuPV1 and treated topically with DBP into the oral cavity. Mice treated with DBP alone or virus alone showed lower to no incidence of squamous cell carcinoma, respectively. Virally infected epithelium showed strong levels of viral DNA staining; squamous cell carcinoma showed reduced levels. p120 ctn expression discriminated normal uninfected epithelium from squamous cell carcinoma or papilloma.